Qualitative Assessment of Domestic Water Supply in the Major Districts of Karachi City for a Sustainable Urban Water Quality Management - Qureshi, Haris Uddin; Abbas, Ibrahim; Shah, Syed Muzzamil Hussain; Kandhro, Muhammad Asim; Teo, Fang Yenn (Journal of Sustainability Perspectives, 2025)
The rising population, changing climate patterns and land use changes have emerged to be a serious consequence for the freshwater resources across the globe. Apart from water quantity, the water quality also holds a significant importance for the human health and the overall ecosystem. Due to the high population growth, massive migrations, and greater anthropogenic activities, the urban centers of the developing and underdeveloped countries are highly susceptible to water quality deterioration and waterborne diseases. Therefore, this study was conducted to assess the water quality of domestic water supply in the three (03) major and highly populated districts of Karachi city of Pakistan including District Central, South, and East, receiving water from Keenjhar Lake via COD treatment plant. The physical test results showed higher turbidity levels (6.33 NTU) in Dhoraji (District East), 5.9 NTU in Boat Basin (District South), and 7.58 NTU in COD influent. Chemically, all samples showed satisfactory results as per the WHO guidelines. However, the biological water quality analysis showed significant presence of bacterial content (E-Coli and Total Coliform) in all collected samples. Conclusively, the treatment efficiency of COD treatment plant was found to be satisfactory and the contamination was mainly found due to the sewage and fecal mixing, presence of mud and silt in conduits, and leakage of sewage from the waste water pipes into the domestic water supply. The presence of harmful biological contaminants found in water is alarming, as it may consequentially lead to Diarrhea, vomiting, Typhoid, Cholera, and Jaundice. Thus, the research outcomes clearly unearthed the existing water quality of the mega city and would significantly serve to formulate well-integrated and holistic source water protection practices and to take effective measures for sustainable water quality management.